Takhrij and Syarah Hadith of Agrotechnology Utilizing land for planting crops - Rahman Sonjaya; Wahyudin Darmalaksana; Rani Widiana (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad.about using agricultural land to grow crops.This research method is quantitative through the approach of takhrij and sharah hadith with agrotechnology analysis. Results and discussion of the importance of utilizing agricultural land for farming is during the time of the Prophet Muhammad. The conclusion of this study is the takhrij and syarah traditions of the Prophet Muhammad. Regarding the importance of using agricultural land to grow crops that provide many benefits to humans.